Possible differences in the performances of vibration-reducing gloves when used with hammers of different sizes - Guido Alfaro Degan; Andrea Antonucci; Gianluca Coltrinari; Dario Lippiello (Heliyon)
Protection provided by vibration-reducing gloves (VR) when used with impact tools can be considerably different from that measured following the ISO 10819 Standard. This paper investigates the transmissibility, at the palm level, of three different types of vibration-reducing gloves (air bubbles; gel; neoprene) and a working leather glove, while using 8 different models of electro-pneumatic hammers for chiseling rock in a limestone quarry plant. The capability to reduce the triaxial vibration as the average of all the tested hammers results limited: 12 % for both the gloves in gel and neoprene, and 7 % for the glove in air. The working leather glove shows a tri-axial transmissibility (Tc(T)) quite equal to the unit. Anyway, the capability to reduce vibrations is tool-dependent. Among the used hammers, the glove in air showed a Tc(T) variable from 0.71 to 1.02, the glove in gel from 0.76 to 1.01, and the glove in neoprene from 0.74 to 1.05, while for the glove in leather the transmissibility remains quite always close to the unit. Grouping the hammers in two different categories in terms of average weight and average impact energy: small-size (4.4 kg; 4 J) and middle-size (10.6 kg; 18.5 J), the average transmissibility results different: Tc(T) = 0.94 for middle-size hammers, and Tc(T) = 0.86 for small-size hammers (p-value <0.00001). This mean that VR gloves could be around 10 % more efficient when used with lightweight and small impact energy hammers. Anyway, mainly because of the relatively small number of hammers investigated, further studies are needed for confirming this result.